Numerical course-keeping tests of ONR tumblehome in waves with different rudder control strategies. (1st February 2023) - Wang, Shuguang; Kim, Byung-soo; Zhu, Zhang; Kim, Yonghwan
Abstract: This study aims to present numerical analysis on the course-keeping performance of an Office of Naval Research (ONR) tumblehome ship model in waves using an enhanced open-source library. The unsteady Reynolds-averaged Navier–Stokes (URANS) model coupled with a hierarchical rigid body motion solver is adopted to simulate free-running ships. An enhanced body-force propeller model for nonuniform inflow is implemented, and an optimized overset grid technology with motion decomposition is used for grid transformation. A rudder control module with a new derived gain-scheduling method for wave cases is introduced for heading control purposes. Five benchmark tests with different wave directions are analyzed in terms of linear and nonlinear motions. The results show good agreement with benchmark data and possible reasons for numerical discrepancies are also discussed. As the P controller of the rudder in oblique waves is insufficient for maintaining a zero-heading, the behavior of P-, PD-, and PID controllers are studied in oblique waves. The optimal control strategy depends on the environmental conditions in which weak rudder control is preferred in rough seas. This work demonstrates that the developed solver is feasible for CFD applications to ship hydrodynamics in waves. Highlights: This paper introduces the CFD results of coursekeeping for an ONR tumblehome vessel. The unsteady RANS solver coupled with a hierarchical motion solver is applied for the free-running simulation in waves. A gain-scheduling method of rudder control in waves is provided and tested in different control scenarios. The CFD predictions are in reasonable agreement with benchmark data.